ROLE OF PREPAREDNESS FOR CHANGE AND PROACTIVE BEHAVIOR TO THE PERFORMANCE OF EMPLOYEE - Ismawati Ismawati; Yuliana Yuliana (SEAN Institute, 2022)
The objective of this study is to investigate how the readiness of employees to adapt to changing circumstances influences the performance of their employers through proactive behavior. Being prepared to deal with change can result in aggressive behavior during implementing the company's Financial Budget System (SIGAKU), which will significantly influence the workforce's performance. Saturated samples use as the method of sampling, and a total of 80 people served as research samples. These individuals comprise lecturers and employees at Sultan Maulana Hasanuddin State Islamic University, responsible for implementing SIGAKU. Method of data analysis using Structural Equation Modeling with Partial Least Square approach. According to the findings, being ready to deal with change directly impacts performance; being prepared to deal with change also positively affects proactive behavior, and aggressive behavior positively impacts performance. However, proactive behavior does not mediate the relationship between performance and readiness to deal with change